Evaluating Business as Usual Activities between Agile and Information Technology Infrastructure Library (A-ITIL): Industry Practitioners’ Point of View - Peliarachchi, Amalka; Wijayanayake, Janaka (Department of Industrial Management, Faculty of Science, University of Kelaniya Sri Lanka, 2023)
Although the Information Technology Infrastructure Library (ITIL) aims to manage the entire lifecycle of an IT service, the protocols of ITIL do not directly control the initiatives that lead to the formation or changes of IT services. However, researchers have explored combining the Waterfall lifecycle, a conventional software development methodology, with the extensive ITIL literature. Unfortunately, they have faced challenges in integrating the agile methodology with ITIL to accurately manage the project lifecycle. In order to address this issue and facilitate Business As Usual (BAU) activities in the IT sector; a proposed framework called A-ITIL (Agile-ITIL combined framework) has been introduced. This research primarily focuses on the requirement for combining the Agile approach with ITIL in BAU tasks within the IT industry. By utilizing shared questionnaires and related research articles, the critical success factors for integrating Agile with ITIL in BAU activities have been identified. The research process began by gathering sample data through an online questionnaire to assess the Agile-ITIL literacy of the respondents and the necessity of combining Agile and ITIL in BAU. A second questionnaire was then used to rate the transparency of transitioning BAU between Agile and ITIL, document the challenges faced during this transition, and propose mitigating strategies for these primary challenges, involving key stakeholders. Subsequently, a user story was created based on the results of the shared questionnaires to identify key points for the A-ITIL framework. Furthermore, the research articles were analyzed to identify key success factors for Agile and ITIL separately. Finally, an A-ITIL conceptual model was designed by mapping the existing research findings, incorporating key success factors from both Agile and ITIL, the key points identified in the user story, and insights from an interview with Agile/ITIL experts. These findings form the foundation for integrating Agile-ITIL and ensuring smooth BAU activities within IT organizations.
Keywords: agile, A-ITIL, BAU, ITIL, waterfall life cycle